DETERMINATION OF HEAVY METALS (Co, Cu,Cd,Fe, Pb, Zn) IN SOME EDIBLE INSECTS AND FINGERLINGS IN DUTSIN-MA TOWN (FUDMA JOURNAL OF SCIENCES, 2022)
Assessment of some carcinogenic (Cd and Pb) and non-carcenogenic (Co, Cu, Fe and Zn) heavy metals elements was carried out on fingerling, grasshopper, locust and termite. These organisms were selected for this study because they are regarded as alternative source of protein and recently as traditional medicine. Hence it became imperative to assess their human health risk. The result analyzed show that cobalt level ranges from 1.85±0.16 mg/kg to 9.03±0.54 mg/kg, copper from 18.56±0.01 mg/kg to 78.02±2.35 mg/kg, iron from is 176±12.55 mg/kg to 390.37±10.95 mg/kg, cadmium1 from74±0.00 mg/kg to 7.11±0.89 mg/kg, lead from 0.04±0.08 mg/kg to 1.14±0.49 mg/kg and zinc 244.15± 10.30 mg/kg to 281.48 ± 45.52 mg/kg. These were determined using atomic absorption spectrophotometer (AAS) and were compared with FAO/WHO standards. And all were above the recommended level except lead (Pb). Fingerling which is the only aquatic organism among the samples was found to contain higher amount of Co, Cu, Fe and Pb. It could be attributed to more interaction with its habitat and usually improper disposal of waste, use of fertlizers and manure among other things may be responsible for that.  Hazard indices (HI) were all high and ranges from 5 to 9 and 16 to 31 for adults and children respectively. Cancer risk (TR) assessments of Cd and Pb were categorized as moderate and low respectively according NYSDOH. Public should therefore avoid eating these organisms because the heavy metals in them may bioaccumulate and manifest adversely.
Keywords: fingerling, grasshopper, heavy metal, locust, termite, carcinogenic, carcinogenic